Mechanical properties and composite formation of metallic whiskers - Schamel, Mattias (My University, 2010)
One-dimensional structures on the nanoscopic scale offer promising scientific topics like their outstanding properties or the integration of structures into composite or functional devices. The main aim of this thesis was to execute reliable tests on small-scaled Cu whiskers and to analyse their mechanical behaviour. A bending test procedure was developed, which comprises the transfer of whiskers onto suitable substrates and in situ SEM bending with a micromanipulator. A new analysis procedure permits the stress analysis of the deflection curves and an evaluation of the boundary conditions at the support. Cu whiskers with diameters between 60 and 230 nm were successfully tested. Stress analysis of successively loaded and unloaded whiskers determined uniquely high yield limits in the order of 4 GPa. Such strength is attributed to the small size of the specimens and to the low defect density within as-grown whiskers. Investigations on plastically deformed whiskers indicate a localised {111} slip or twinning process as underlying deformation mechanism. Also, individual grains with high defect density can occur locally, depending on the sample geometry. A second task of this thesis was to undertake first steps towards the application of whiskers in composite structures. Nanoscale bimetallic stripes and coated whiskers were produced by altering the MBE deposition parameters for Cu and Ni. SEM and TEM analysis of the structures and their cross-sections showed a semi-coherent phase boundary and permitted conclusions about the growth of Ni on top of Cu whiskers. The curved shape of the bimetallic stripes at room temperature is explained by the microstructure and by the difference in lattice parameter between Cu and Ni. Simple models are presented to clarify that matter. The thermal behaviour of bimetallic stripes was investigated in situ in TEM and microstructural changes were identified to dominate the curvature changes during heating.
Keywords: Materialteknik; Konstruktionsmaterial; Materials Engineering; Construction materials